Molecular Phylogeny, Character Evolution, and Biogeography of Hydrangea Section Cornidia, Hydrangeaceae - Granados Mendoza, Carolina; Martínez Salas, Esteban Manuel; Goetghebeur, Paul; Wanke, Stefan; Samain, Marie-Stéphanie (Frontiers in Plant Science, 2021)
Hydrangea section Cornidia consists of 26 currently accepted species and a yet undefined number of new species and erroneously synonymized taxa. This clade consists of (sub)tropical lianas occurring from northern Mexico to southern Chile and Argentina, and one species from Southeast Asia. Currently no molecular phylogenetic hypothesis is available that includes more than a few species of this section. Hence, a resolved and well-sampled molecular phylogenetic hypothesis may help to enforce taxonomic decisions. Here we present a phylogenetic framework based on sequences from two low copy nuclear genes from a comprehensive taxon sampling of H. section Cornidia and a selection of outgroups. Our phylogenetic reconstructions proof the non-monophyly of the traditionally recognized subsections Monosegia and Polysegia and their corresponding series Speciosae and Aphananthae, as well as Synstyleae and Chorystyleae, respectively. Three morphologically defined species were recovered with high support as monophyletic, namely H. panamensis, H. serratifolia and H. tarapotensis. However, statistical support for some shallow nodes did not allow to refute, with high support, the monophyly of several of the recognized species for which more than one individual could be analyzed. Based on the obtained phylogenetic framework we reconstructed the evolution of selected reproductive characters. Hydrangea section Cornidia is the only genus section for which dioecism has been extensively documented. Our character reconstruction of sexual dimorphism shows that dioecism is the ancestral state in this section and that this was reversed to monoecy in H. seemannii and H. integrifolia. Character reconstruction for the enlarged marginal flowers recovered their presence as the ancestral character state in Cornidia, although at least three internal lineages independently lost them, thus losses were reconstructed to be more likely than gain. With respect to the flower color, more species exhibit white than red flowers and white is reconstructed as the ancestral state. Cornidia also shows an unusual disjunct geographic distribution between Asia and Central-Mesoamerica – South America, as it is not present in the USA and Canada. The origin of Cornidia is reconstructed to be the New World with higher probability and the presence of one species in Asia is likely due to long distance dispersal.